2020
DOI: 10.1038/s41598-020-71017-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrowetting-on-dielectric characteristics of ZnO nanorods

Abstract: Herein, we report the electrowetting-on-dielectric (eWoD) characteristics of Zno nanorods (nRs) prepared via the hydrothermal method with different initial Zn 2+ concentrations (0.03, 0.07, and 0.1 M). Diameter of the resultant ZnO NRs were 50, 70 and 85 nm, respectively. Contact angle (CA) measurements showed that the Teflon-coated ZnO NRs with diameters of 85 nm prepared from the 0.1 M solution had the highest CA (137°). During the EWOD studies, on the application of a voltage of 250 V, the water CA decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Inorganic dielectric materials were attempted to use in electrowetting systems due to the high dielectric constant, such as ZnO and Al2O3 [14][15][16][17][18] . Yet, producing an inorganic layer was complicated and not comparable to the mass production of EWD.…”
Section: The Dielectric Layer and Liquid Materialsmentioning
confidence: 99%
“…Inorganic dielectric materials were attempted to use in electrowetting systems due to the high dielectric constant, such as ZnO and Al2O3 [14][15][16][17][18] . Yet, producing an inorganic layer was complicated and not comparable to the mass production of EWD.…”
Section: The Dielectric Layer and Liquid Materialsmentioning
confidence: 99%
“…The I-V test showed the IPP also improved the isolating property of the composite dielectric layer and decreased the leakage current after aging tests. Besides, related researchers have reported EFD properties of some potential dielectric materials and multilayer insulators, such as teflon-coated electrosprayed silica layers [14] , ZnO nanorods [15] , carbon nanotubes, SU8 photoresist, Parylene C, and so on [5] .…”
Section: Dielectric Materialsmentioning
confidence: 99%
“…It was shown that structured superhydrophobic surfaces exhibit a higher droplet movement speed [31] and higher cleaning efficiency than unstructured hydrophobic surfaces for different (bio-)particles with EWOD, demonstrating that it is advantageous to use these structured surfaces in DMF [32]. Various surface structures on the nanoscale [32][33][34][35][36][37][38][39][40][41], the microscale [42][43][44][45] and on both nanoscale and microscale [46,47] were examined in EWOD. These surfaces consisted of an insulating layer and a repellent low surface energy one.…”
Section: Introductionmentioning
confidence: 99%
“…These surfaces consisted of an insulating layer and a repellent low surface energy one. Materials used for insulation include silicon dioxide [33,35,37,44,47], photoresists, such as, for example, SU-8 [42] and zirconium oxide [39,45], while commonly used hydrophobic materials are fluoropolymers, such as C 4 F 8 [33,35,37,44,47], Teflon [39,42], Cytop ® [32], or alkyl-/fluorosilanes [32,38,45] and carbon [36]. There are also systems that consist of one single layer that simultaneously serves as an insulating and repellent layer, examples of which include coatings with carbon nanotubes [34], graphene [46] and polypyrrole [48].…”
Section: Introductionmentioning
confidence: 99%